2015
DOI: 10.1093/neuonc/nov125
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming in glioblastoma: the influence of cancer metabolism on epigenetics and unanswered questions

Abstract: A defining hallmark of glioblastoma is altered tumor metabolism. The metabolic shift towards aerobic glycolysis with reprogramming of mitochondrial oxidative phosphorylation, regardless of oxygen availability, is a phenomenon known as the Warburg effect. In addition to the Warburg effect, glioblastoma tumor cells also utilize the tricarboxylic acid cycle/oxidative phosphorylation in a different capacity than normal tissue. Altered metabolic enzymes and their metabolites are oncogenic and not simply a product o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
220
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(225 citation statements)
references
References 118 publications
4
220
0
1
Order By: Relevance
“…These aspects of GBM malignancy are supported by the manipulation of a number of biological pathways to exploit not only intracellular tumor resources but also the microenvironment provided by surrounding cells [28]. Augmented glycolysis or Warburg effect [3, 28, 29] and abnormal tryptophan catabolism [30] are hallmarks of GBM. Specifically, Xiong and colleagues observed that a mutated form of a critical component of the TCA cycle, isocitrate dehydrogenase 1 (IDH1), is associated with HIF-1α-mediated carcinogenesis.…”
Section: Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…These aspects of GBM malignancy are supported by the manipulation of a number of biological pathways to exploit not only intracellular tumor resources but also the microenvironment provided by surrounding cells [28]. Augmented glycolysis or Warburg effect [3, 28, 29] and abnormal tryptophan catabolism [30] are hallmarks of GBM. Specifically, Xiong and colleagues observed that a mutated form of a critical component of the TCA cycle, isocitrate dehydrogenase 1 (IDH1), is associated with HIF-1α-mediated carcinogenesis.…”
Section: Glioblastomamentioning
confidence: 99%
“…Multiple lines of evidence indicate that the increase in aerobic glycolysis detected in GBM supports the elevated nutrient demands of fast proliferating cancer cells by providing lipid and nucleotide biosynthesis [28]. In addition, this increased glycolysis has important effects on tumor-specific immunity and consequently, tumor pathogenesis [31, 32].…”
Section: Glioblastomamentioning
confidence: 99%
“…Glutaminolysis, the catabolism of glutamine to support tumor cell proliferation, is also a central feature of cancer metabolic reprogramming [18]. Additionally, tumor cells require large amounts of lipid and nucleotides for membrane biogenesis, signal transduction, cell proliferation and potentially as an energy source [1]. The metabolic adaptations that reprogram how cancer cells take up and utilize nutrients to drive tumor growth are activated by profound changes in signaling and epigenetic/transcriptional networks induced by activated oncogenes (e.g.…”
Section: Introduction – Genetic Aberrations Drive Cancer Metabolism Imentioning
confidence: 99%
“…3 Hypoxic regions are a key feature of GBMs and associated with areas of pseudopallisading necrosis, which also show increased expression of hypoxia-inducible factor α (HIF1α), a key player in inducing the Warburg effect. 38 HIF1α is stabilized in the setting of hypoxia and acts as a transcription factor that triggers a number of changes in gene expression and protein signaling aimed at increasing levels of tumor cell defense mechanisms include resistance pathways, accelerated metabolism, and angiogenic factors.…”
Section: New Approaches To Glioma Therapy: Targeted Therapies and Beyondmentioning
confidence: 99%
“…2 Another emerging area is the identification and targeting of tumor-specific metabolic and protein-processing pathways that act as hubs for converging cellular processes vital for tumor cell survival. 3 Targeting such hubs has the potential to disable the complex signaling networks that tumor cells depend on for survival and resistance to therapy. However, the slow progress in developing effective therapies against gliomas has also resulted in patients seeking alternative and often untested therapies that are used concurrent with or as alternatives to standard therapy 4 ; the rigorous assessment of such treatments through systematic studies is emerging as an equally important aspect of cancer care.…”
mentioning
confidence: 99%